STABILITY AND MOLECULAR CHARACTERIZATION TO SCREEN OUT HEAT TOLERANT GENOTYPES OF CHICKPEA (CICER ARIETINUM L.) - NIHARIKA SHUKLA; R. S. SHUKLA; ARUN CHAVAN (The Bioscan, 2014)
Thirty diverse genotypes sown in three different dates were screened using twenty SSR primers. Field observations were recorded for 14 phenological and morphological characters. Among which days to 50% flowering has less susceptibility for these genotypes against environmental fluctuations. The component G × E interaction were found significant for harvest index, total seeds per pod and effective pods per plant, hundred seed weight, biological yield and seed yield. The highest gene diversity was found in TA 146 (0.898), followed by primer TR 19 (0.884) and ICCM 0249 (0.877). Based on a dendrogram all the 30 genotypes were grouped into two clusters A and B. The genotype JG 19 showed highest gene similarities (96.77%) with JG 21, similarly MP-JG 99-115 showed 96.77% resemblance with JG 17 and JG14-11 which are observed in same cluster. The genotypes, ICCV 07102, JG 21 and JG 22 were found suitable for all the dates of sowing while genotypes JG 16, JG 21, GG 2, ICC 4958, and JG 22 were suitable for late and very late sowing.